Global innovation races, offshoring and wage inequality - Impullitti, Giammario (Wiley, 2016)
In the 1970s and 1980s the US position as the global technological leader was increasingly challenged by Japan and Europe. In those years the US skill premium and residual wage inequality increased substantially. This paper presents a two-region quality ladders model of technical change where firms from the leading region innovate in all sectors of the economy, while the lagging region progressively catches up as its firms enter global innovation races in a larger number of sectors. As the innovation gap closes, the advanced country experiences fiercer foreign technological competition which forces its firms to innovate more. Faster technical change then increases the skill premium and residual inequality. Offshoring production and innovation plays a key role in shaping the link between international competition and inequality. The quantitative analysis exploits the variation in the geographical distribution of R&D investment in OECD STAN data to construct a measure of international technological competition between the US and the rest of the world. In a calibrated version of the model, the observed increase in foreign competition experienced by US firms accounts for up to 1/6th of the surge in the US skill premium and up to one half of the increase in residual inequality between 1979 and 1995.